Scope of asymmetries in the Euro area - Stefaan Ide; Philippe Moës (National Bank of Belgium, 2003)
We discuss the scope of asymmetries in growth and inflation developments in the euro area countries, taking the euro area as the natural benchmark since the establishment of EMU. We start with a descriptive analysis of a set of indicators that can give a first idea of the likelihood of or extent to which Member States can show asymmetries with respect to the euro area. This approach typically leads to a division of countries between a core and a periphery, the former consisting over the 1993-2000 sub-period of Belgium, Germany, France, Italy, Spain and Austria and perhaps the Netherlands. However, it is rather difficult to weight the indicators and to draw a firm line between "insiders" and "outsiders" in this way. Moreover the dichotomy does not provide any information on the true extent of the asymmetries inside the core and periphery. Accordingly, we move to a quantitative approach (SVAR models) that makes it possible to assess two forms of asymmetry: asymmetry stemming from country-specific shocks and asymmetry stemming from differences in the way countries react to symmetric euro area shocks. The asymmetries are measured along two dimensions: growth and inflation developments. We find that over the years 1971-2000 growth in many countries is driven by the symmetric shocks while the opposite holds true for inflation where asymmetric (country-specific) shocks dominate. However regarding growth, the responses of the different countries to the symmetric shocks do not really differ and these shocks are not a major source of divergence. As a consequence, for growth as well as for inflation, the asymmetries with respect to the euro area are mainly the result of genuine asymmetric shocks. We notice a marked decrease in the impact of asymmetric shocks on inflation over the years, a phenomenon that is also present for growth, albeit less pronounced. If the years 1993-2000 can be used to evaluate the current situation, it appears that countries are spread along a line going from close similarity to the euro area (France) to extensive asymmetry (Ireland). Asymmetric shocks are not negligible yet with an average annual impact of around 1 percentage point on country growth or inflation. Some countries usually thought to belong to the core, are still exposed to such average shocks, in terms of growth or in terms of inflation.
Keywords: 330; Wirtschaftswachstum; Inflation; Räumliche Verteilung; Eurozone; Euro; EU-Staaten